Joint observables induced by indirect measurements in cavity QED - Raikisto, Kalle; Luoma, Kimmo (Frontiers in Quantum Science and Technology, 2025)
A fundamental feature of quantum mechanics is that there are observable pairs that cannot be measured jointly, such as observables corresponding to position and momentum or spin direction measurements. However, unsharp versions of non-jointly measurable observables may become jointly measurable. In this study, we investigate the joint measurability of time-continuous observables emerging from indirect time-continuous measurements. In particular, we study a paradigmatic situation where a qubit is interacting with a mode of light in a cavity, and the light escaping the cavity is continuously monitored. We find that the properties of the observables can be tuned by changing the type of the monitoring scheme or by tuning the initial state of the cavity. In particular, we demonstrate that heterodyne measurements are a joint measurement of a noisy homodyne measurement of a pair of canonical quadratures. Moreover, we investigate the purity of the induced qubit observables as a function of the noise.